Potential and development of cellular vesicle vaccines in cancer immunotherapy - Wenxi Zhao; Xianjun Li; Jialu Guan; Shuai Yan; Lizhi Teng; Xitong Sun; Yuhan Dong; Hongyue Wang; Weiyang Tao (Discover Oncology)
Abstract Cancer vaccines are promising as an effective means of stimulating the immune system to clear tumors as well as to establish immune surveillance. In this paper, we discuss the main platforms and current status of cancer vaccines and propose a new cancer vaccine platform, the cytosolic vesicle vaccine. This vaccine has a unique structure that can integrate antigen and adjuvant carriers to improve the delivery efficiency and immune activation ability, which brings new ideas for cancer vaccine design. Tumor exosomes carry antigens and MHC-peptide complexes, which can provide tumor antigens to antigen-processing cells and increase the chances of recognition of tumor antigens by immune cells. DEVs play a role in amplifying the immune response by acting as carriers for the dissemination of antigenic substances in dendritic cells. OMVs, with their natural adjuvant properties, are one of the advantages for the preparation of antitumor vaccines. This paper presents the advantages of these three bacteria/extracellular vesicles as cancer vaccines and discusses the potential applications of functionally modified extracellular vesicles as cancer vaccines after cellular engineering or genetic engineering, as well as current clinical trials of extracellular vesicle vaccines. In summary, extracellular vesicle vaccines are a promising direction for cancer vaccine research.